Defining definitions: a Delphi study to develop a core outcome set for conditions of severe maternal morbidity. (24th August 2017) - Schaap, T; Bloemenkamp, K; Deneux‐Tharaux, C; Knight, M; Langhoff‐Roos, J; Sullivan, E; van den Akker, T
Abstract : Objective: Develop a core outcome set of international consensus definitions for severe maternal morbidities. Design: Electronic Delphi study. Setting: International. Population: Eight expert panels. Methods: All 13 high‐income countries represented in the International Network of Obstetric Surveillance Systems (INOSS) nominated five experts per condition of morbidity, who submitted possible definitions. From these suggestions, a steering committee distilled critical components: eclampsia: 23, amniotic fluid embolism: 15, pregnancy‐related hysterectomy: 11, severe primary postpartum haemorrhage: 19, uterine rupture: 20, abnormally invasive placentation: 12, spontaneous haemoperitoneum in pregnancy: 16, and cardiac arrest in pregnancy: 10. These components were assessed by the expert panel using a 5‐point Likert scale, following which a framework for an encompassing definition was constructed. Possible definitions were evaluated in rounds until a rate of agreement of more than 70% was reached. Expert commentaries were used in each round to improve definitions. Main outcome measures: Definitions with a rate of agreement of more than 70%. Results: The invitation to participate in one or more of eight Delphi processes was accepted by 103 experts from 13 high‐income countries. Consensus definitions were developed for all of the conditions. Conclusion: Consensus definitions for eight morbidity conditions were successfully developed using the Delphi process. These should be used in national registrations and international studies, and should be taken up by the Core Outcomes in Women's and Newborn Health initiative. Tweetable abstract: Consensus definitions for eight morbidity conditions were successfully developed using the Delphi process. Tweetable abstract: Consensus definitions for eight morbidity conditions were successfully developed using the Delphi process.